2020
DOI: 10.1038/s41388-020-1202-y
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of a novel triple-acting PIM/PI3K/mTOR inhibitor, IBL-302, in breast cancer

Abstract: The proviral integration of Moloney virus (PIM) family of protein kinases are overexpressed in many haematological and solid tumours. PIM kinase expression is elevated in PI3K inhibitor-treated breast cancer samples, suggesting a major resistance pathway for PI3K inhibitors in breast cancer, potentially limiting their clinical utility. IBL-302 is a novel molecule that inhibits both PIM and PI3K/AKT/mTOR signalling. We thus evaluated the preclinical activity of IBL-302, in a range of breast cancer models. Our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 64 publications
(87 reference statements)
0
19
0
Order By: Relevance
“…A large number of studies link PIM1 activity to a more invasive tumor phenotype and worse prognosis in cancers [ 19 , 20 , 21 , 22 , 23 ]. Thus, the PIM kinase pathway has become an attractive target for cancer therapy with a number of drugs under investigation in the clinic including TP-3654 in advanced solid tumors (NCT03715504) and myelofibrosis (NCT04176198) and PIM447 in myelofibrosis (NCT02370706) as well as a number of drugs at preclinical stages of testing [ 11 , 24 , 25 , 26 ]. Here we show that all three PIM kinases are expressed in HCC827, H460 and H1975 cell lines and PIM1 positive NSCLC patients had a worse median survival than those that were PIM1 negative ( p = 0.056).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies link PIM1 activity to a more invasive tumor phenotype and worse prognosis in cancers [ 19 , 20 , 21 , 22 , 23 ]. Thus, the PIM kinase pathway has become an attractive target for cancer therapy with a number of drugs under investigation in the clinic including TP-3654 in advanced solid tumors (NCT03715504) and myelofibrosis (NCT04176198) and PIM447 in myelofibrosis (NCT02370706) as well as a number of drugs at preclinical stages of testing [ 11 , 24 , 25 , 26 ]. Here we show that all three PIM kinases are expressed in HCC827, H460 and H1975 cell lines and PIM1 positive NSCLC patients had a worse median survival than those that were PIM1 negative ( p = 0.056).…”
Section: Discussionmentioning
confidence: 99%
“…Of the signaling pathways, PI3K-AKT was the most significantly enriched signaling pathway, which was frequently activated in patients with TNBC. The pathway was considered as a promising therapeutic target, and several inhibitors targeting this pathway were designed and evaluated in various clinical trials [61,[63][64][65]. More importantly, these findings confirmed that TCM exhibits synergistic effects against diseases through multiple-ingredient, multiple-target, and multiple-pathway approaches [9,10,23,30].…”
Section: Discussionmentioning
confidence: 68%
“…Approximately 2 of 3 breast cancers are hormone receptor-positive (ER+ or PR+). Treatment with hormone therapy is often helpful in these cases, and certain targeted therapy drugs, such as CDK4/6 inhibitors [ 13 ], mTOR inhibitor (Everolimus) and PI3K inhibitor (Alpelisib) [ 38 ], can increase the efficacy of hormone therapy. Among all types of breast cancer, triple-negative breast cancer (TNBC) has the worst prognosis due to the lack of an effective target.…”
Section: Discussionmentioning
confidence: 99%